Permodalan Nasional Berhad (PNB) 201-A, Jalan Tun Razak, 50400 Kuala Lumpur / Norliana Amira Mohamad Suraji - Mohamad Suraji, Norliana Amira (Bachelor of Information Science (HONS.) Records Management, 2015)
PNB was conceived as a fundamental instrument of the government New Economics Policy to promote share ownership in the corporate sector among the Bumiputera, and develop opportunities for suitable Bumiputera professionals to participate in the creation and management of wealth. The main subsidiary of PNB is ASNB which is to manage the unit trust funds launched by PNB. On the other hand, department SARA 1 Malaysia is a special scheme initiated by the Government of Malaysia aimed at promoting the participation of the low income group to save and invest apart from to assist them in managing the impact of the rising current cost of living. It is the service provider to the Special Purpose Vehicle (SPV) established by the Ministry of Finance (MOF) to implement the project. Intern student in SARA 1 Malaysia department involved was totally in a field of management that consists of customer service and full office work such as administrative work, customer service and also assisted in performing others tasks such as updating SARA new application status either reject or approve. If the applicant is rejected we have to find the reason. Furthermore, the student was required to participate in marketing activities when we to the country around the world to meet the target people to apply SARA 1 Malaysia as well as communicating with the public. Thus, this marketing will improve our public relation. The student had gain new insights and more comprehensive understanding about the real industry working condition.